Bamboo stem ash as a sustainable cement replacement in lightweight foam mortar enhancing mechanical thermal and microstructural properties. - Mydin, Md Azree Othuman; Azman, Nurul Zahirah Noor; Awoyera, Paul O.; Özkılıç, Yasin Onuralp; Fadugba, Olaolu George; Abdullah, Mohd Mustafa Al Bakri; Omar, Roshartini; Datta, Shuvo Dip (Scientific Reports, 2025)
This study presents a novel approach to enhancing the properties of lightweight foam mortar (LFM) by utilizing bamboo stem ash (BSA) as a partial cement replacement. Unlike traditional supplemental cementitious materials (SCMs) like fly ash or silica fume, BSA provides a special blend of lightweight properties and a high silica concentration. Thus, the effect of BSA (in proportions of 0–25% and steps of 5%) on the mortars’ fresh, hardened, microscale properties, such as workability, density, strength, durability, and microstructural characteristics, was explored. At 15% BSA replacement, the compressive strength reached 8.25 MPa at 28 days, 7% higher than the control mix (7.7 MPa). The study identifies 15% BSA as the optimal replacement level, striking a balance between mechanical strength, durability, and thermal insulation. Beyond 15%, increased porosity begins to reduce strength, while thermal resistance continues to improve. Thus, a 10–15% replacement range is recommended for applications requiring structural integrity and insulation. The density of the foam mortar decreased from 1000 kg/m3 for the control mix to 960 kg/m3 at 20% BSA replacement, improving the material’s lightweight characteristics. Also, the porosity increased from 24.8% (control) to 30.2% (25% BSA), positively influencing thermal insulation properties. Thermal conductivity measurements indicated a reduction from 0.25 W/mK (control) to 0.18 W/mK at 25% BSA replacement, demonstrating improved thermal resistance. BSA incorporation improves the pore structure and fosters stronger interfacial bonding within the matrix, especially at 15% replacement, according to microstructural investigation using SEM. The water absorption rate increased slightly from 18.2% (control) to 21.6% (25% BSA), still within reasonable bounds for lightweight construction applications. As demonstrated by the mortars’ notable performance, BSA may effectively replace OPC in LFM, improving its mechanical, thermal, and environmental qualities. With the results, BSA has shown potential for developing eco-friendly building materials and aiding in reducing carbon emissions in the built environment. These results show that BSA can be a green and practical substitute for OPC in lightweight building applications, especially for prefabricated panels, insulation layers, and non-load-bearing walls. Its ability to enhance mechanical strength while reducing thermal conductivity makes it a promising material for energy-efficient and sustainable building solutions.